Questioning the Effort Hypothesis That Depressed Patients Perform Disproportionately Worse on Effortful Cognitive Tasks. Issue 2 (April 2020) - Hammers, Dustin B.; Weisenbach, Sara
The debate over Hasher and Zacks' effort hypothesis—that performance on effortful tasks by patients with depression will be disproportionately worse than their performance on automatic tasks—shows a need for additional research to settle whether or not this notion is "clinical lore." In this study, we categorized 285 outpatient recipients of neuropsychological evaluations into three groups—No Depression, Mild-to-Moderate Depression, and Severe Depression—based on their Beck Depression Inventory-2 self-reports. We then compared these groups' performances on both "automatic" and "effortful" versions of the Ruff 2 & 7 Selective Attention Test Total Speed and Total Accuracy Indices, the Digit Span subtest from the Wechsler Adult Intellectual Scale—Fourth Edition, and Trail Making Test Parts A and B, using a two-way (3 × 2) mixed multivariate analysis of variance. Patients with Mild-to-Moderate Depression or Severe Depression performed disproportionately worse than patients with No Depression in our sample on more effortful versions of only one of the four attention or executive functioning measures (Trail Making Test). Thus, these data failed to fully support a hypothesis of disproportionately worse performance on more effortful tasks. While this study failed to negate the effort hypothesis in some specific instances, particularly for use in the Trail Making Test, there is cause for caution in routinely applying the effort hypothesis when interpreting test findings in most clinical settings and for most measures.